Stress at Workplace for Shift Staff (Petronas Sabah Auxiliary Police) - Suzalina Rusli (Open University Malaysia, 2020)
In this project paper, the objective is to identify factor that influence stress at workplace for shift staff of PETRONAS Sabah Auxiliary Police and their stress level. There are 12 respondents participated in this project paper, where there are three parts of questions in the questionnaire. The first part of the questionnaire consists of variables such as gender, age, marital status and duration of service. Meanwhile for the second and third part of the questionnaire consist of five and ten questions with Likert scale of five and ten. For the identifying stress level questionnaire, it refers to the American Institute of Stress (AIS) survey question which stress at workplace. To analyse the data from the questionnaire, several test such as reliability test, descriptive analysis, bivariate correlation test, paired-sample t-test and one-way ANOVA test were used to for this project paper by using Statistic Package for Social Science (SPSS) software. From the analysed data, the highest score for factor that influence stress at workplace is lack of communication between colleague and superior. On the other hand, there are two highest score for stress level amongst the respondent are able to handle stress well and moderately well. Through bivariate correlation test, both question's analysed data shows a strong relationship between question 3 and 5 for the factor that influence stress and question 6 and 9 for identifying stress level. However, for determining any significant differences between variable, factor influence stress at workplace, paired-sample t-test and one-way ANOVA test were used. Through both test, there are significant difference between age, gender and marital status with the highest score factor that influence stress at work place. In conclusion, it is recommended to provide one-to-one discussion between company and workers regularly in order to understand and help their work. (Abstract by author)